2019
DOI: 10.1186/s12893-019-0470-3
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve of laparoscopic percutaneous extraperitoneal closure (LPEC) for inguinal hernia: protocoled training in a single center for six pediatric surgical trainees

Abstract: BackgroundLaparoscopic percutaneous extraperitoneal closure (LPEC) has become a common procedure for repairing inguinal hernia. As a laparoscopic approach, pediatric surgical trainees require more training to learn LPEC than a traditional open approach. This study aimed to clarify the experience needed to acquire the skill to perform LPEC adequately.MethodsThis descriptive single-center study used clinical data from patients who underwent LPEC between May 2009 and May 2016. The mean operative time for ten cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…Yoshizawa et al 20 studied differences of the learning curve between residents and attendings, finding a learning curve of at least 12 cases for attendings and 31 for residents to reach a mean operative time of 30 minutes. Shibuya et al 21 analyzed the learning process in surgical trainees and observed a mean operative time of less than 25 minutes after 48 procedures and a mean operative time of 20 minutes after 125 cases (►Table 3). Both Yoshizawa et al and Shibuya et al reported no complications.…”
Section: Inguinal Hernia Repairmentioning
confidence: 99%
“…Yoshizawa et al 20 studied differences of the learning curve between residents and attendings, finding a learning curve of at least 12 cases for attendings and 31 for residents to reach a mean operative time of 30 minutes. Shibuya et al 21 analyzed the learning process in surgical trainees and observed a mean operative time of less than 25 minutes after 48 procedures and a mean operative time of 20 minutes after 125 cases (►Table 3). Both Yoshizawa et al and Shibuya et al reported no complications.…”
Section: Inguinal Hernia Repairmentioning
confidence: 99%
“…Open repair through inguinal incision which includes high ligation and resection of the hernia sac has been standard treatment for pediatric hernia for a long period of time [ 15 ]. With the development of minimally invasive surgery numerous laparoscopic techniques for pediatric inguinal hernia repair have been developed including intracorporeal suturing and an extracorporeal approach [ 1 , 2 , 3 , 4 , 14 , 16 , 17 ]. According to recent literature PIRS for pediatric inguinal hernia repair has been proven to be a safe and effective method [ 1 , 2 , 3 , 4 , 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that there is a significant reduction in the number of intraoperative complications and recurrence rates after 35 PIRS procedures per pediatric surgeon [ 13 ]. Another study showed that although there were individual differences, all trainees acquired the skill to perform PIRS adequately within ten months [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumable that the latter two reasons tend to occur more frequently when the surgery is performed by inexperienced surgeons. The learning curve of the laparoscopic percutaneous extra-corporeal technique varies between 31 and 48 operations for paediatric surgical trainees and between 12 and 35 operations for surgeons (34)(35)(36). Since the extra-corporeal technique does not require intraperitoneal suturing, it is expected to have a lower learning curve than the intra-corporeal technique.…”
Section: Discussionmentioning
confidence: 99%